Yahweh and the gods in Hosea - Kruger, P. A. (Journal for semitics, 1992)
This contribution investigates (i) the function of the polemics against the gods in the book of Hosea, (ii) the polemical terms used and (iii) the spectrum of religious worship attacked. It concludes that religious life in Hosea's day was practised on three levels: that of the family, region and state, of which the second and third levels were heavily syncretized. To drive his message home in these circumstances, the prophet employs the following rhetorical strategy: (a) He presents a schematized view of Israel's early religious history in which the worship of the gods is relegated to their ""now"" existence in the land. Over against this sinful present he puts God's historical ""then"" - his salvation deeds. (b) In order to further stress the gravity and abusiveness of Israel's ""now"" existence, he engages in a severe polemics against the gods for which he coined various abusive designations.